THE INFLUENCE OF INTELLECTUAL CAPITAL AND GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE IN BANKING COMPANIES - Santi Susanti; Mulyanti Andhani; Sri Zulaihati (AFEBI Accounting Review, 2018)
The purpose of this research is to test the effect of intellectual capital and good corporate governance (GCG) on financial performance in the banking sector. The sampling technique in this research is random sampling of as many as 36 banks. This research uses Pulic’s model to measure the components of intellectual capital. Self-assessment is used to measure GCG, as established by the Bank of Indonesia, and Financial Performance is measured using the ratio Operating Expenses to Operating Income (BOPO). Based on the results, the variables Intellectual Capital and Good Corporate Governance indicate that GCG has a positive and significant effect on financial performance. Intellectual capital and GCG explain 49.9% of financial performance.Keywords: Financial Performance, Good Corporate Governance, Intellectual Capital